2012
DOI: 10.1007/s10549-012-2331-y
|View full text |Cite
|
Sign up to set email alerts
|

Exercise for health: a randomized, controlled trial evaluating the impact of a pragmatic, translational exercise intervention on the quality of life, function and treatment-related side effects following breast cancer

Abstract: and UC (n=60) groups. Results: There were significant (p<0.05) interaction effects on QoL, fitness and fatigue, with differences being observed between the treatment groups and the UC group. Trends observed for the treatment groups were similar. The treatment groups reported improved QoL, fitness and fatigue over time and changes observed between baseline and post-intervention were clinically relevant. In contrast, the UC group experienced no change, or worsening QoL, fitness and fatigue, mid-intervention. Alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
161
3
8

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 163 publications
(177 citation statements)
references
References 31 publications
(40 reference statements)
5
161
3
8
Order By: Relevance
“…Overall, the cancer studies observed positive outcomes including improved 42 or prevented 10 functional decline, improvement in fitness and fatigue, [43][44][45] diet quality 42,[46][47][48] and QoL. 43,45,49 The goals of the exercise interventions were similar to our study (that is, improve exercise time, and body composition), however, goals of nutrition interventions were different because participants were long-term survivors, or in the early stage of cancer.…”
Section: Randomisedsupporting
confidence: 63%
See 3 more Smart Citations
“…Overall, the cancer studies observed positive outcomes including improved 42 or prevented 10 functional decline, improvement in fitness and fatigue, [43][44][45] diet quality 42,[46][47][48] and QoL. 43,45,49 The goals of the exercise interventions were similar to our study (that is, improve exercise time, and body composition), however, goals of nutrition interventions were different because participants were long-term survivors, or in the early stage of cancer.…”
Section: Randomisedsupporting
confidence: 63%
“…Overall, the cancer studies observed positive outcomes including improved 42 or prevented 10 functional decline, improvement in fitness and fatigue, [43][44][45] diet quality 42,[46][47][48] and QoL. 43,45,49 The goals of the exercise interventions were similar to our study (that is, improve exercise time, and body composition), however, goals of nutrition interventions were different because participants were long-term survivors, or in the early stage of cancer. Nutrition goals in these studies were targeted at modifiable risk factors such as improving diet quality (that is, reducing fat and energy intake while increasing fruit and vegetable intake), [46][47][48] whereas the short-term goals of our participants were aimed at stabilising nutritional deterioration and replenishing nutrition reservoirs through emphasis on high protein and high energy intake.…”
Section: Randomisedsupporting
confidence: 63%
See 2 more Smart Citations
“…According to recent studies [8,9], the evaluation of the quality of life has become an important criterion for assessing the effectiveness of women's physical rehabilitation.…”
Section: Introductionmentioning
confidence: 99%